Validation Plan For Compound Split, Variable Rotor Speed Drivetrain - Gross, C.; Juen, A.; Braumann, L.; Amri, H. (My University, 2024)
This publication presents a validation plan for a transmission variable compound split drivetrain which is used for in flight rotor speed variation of rotorcraft. The validation is performed on a smaller-scale demonstrator at 300kW instead of 1MW. Scaling of the drivetrain can reduce the costs and increase the safety of the tests. To enable the extrapolation of the test results to the full-size application a scaling method for the boundary conditions and the mechanical properties was developed. The scaling method was validated using gear calculation software and modal analyses. The deviation of the gear safety factors is less than 5% while the modal analyses and shaft calculations show that the scaling method predicts a similar behaviour. Based on this scaling method a demonstrator was designed to reflect accurate behaviour of rotor speed variation mechanisms. A test plan to prove the functionality and safety of the Vari-Speed Drivetrain with the scaled demonstrator was developed. The research is part of the international research project VARI-SPEED-II which aims to enable main rotor speed variation for rotorcraft.